ANALISIS PENERAPAN SISTEM PEMERINTAHAN FAMILISME DI PEDESAAN - Francius Simanullang, Reno; Ruspiana Hutagaol; Zenfitri R. Situmorang; Sugiharto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article explains the politics of familism in Indonesia, especially in the regions and tries to answer the question of how familism is formed and what its implications are for village development. The method used is qualitative-descriptive which is analyzed using familism theory. This article concludes that although kinship relations are quite strong in the village government structure, their impact on village development is not good, as evidenced by slow services and unrealized development as well as the existence of village officials who abuse their position in serving the community to take action. take care of administration such as personal data. and implementing a system that is in accordance with village apparatus regulations, not an appropriate system, especially regarding the use of village funds. The point is that kinship politics is not positive and in any case will always give rise to prolonged polemics and hinder other communities that have potential.